Cohort profile: The Forzani & MacPhail Colon Cancer Screening Centre biorepository, Calgary, Alberta. Issue 11 (11th November 2020) - Hilsden, Robert J; Heitman, Steven J; Lamidi, Mubasiru; Diallo, Mamadou Dian; English, Janine; Town, Susanna; Cartwright, Shane; Maxwell, Courtney; McGillivray, Mary-Elizabeth; McGregor, Elizabeth; Barberio, Amanda; Pader, Joy; et al.
Abstract : Purpose: The Colon Cancer Screening Centre (CCSC) biorepository (Calgary, Canada) supports a wide range of research topics related to colorectal cancer (CRC) by collecting, and storing biospecimens (blood, urine, normal colon tissue) from consenting patient participants. Housing unique biospecimens along with detailed participant lifestyle and health history questionnaire data, the CCSC biorepository can support a variety of research related to CRC risk factors, biomarkers, genetic causes and more. Participants: Currently, 2292 average risk CRC patients have consented to participate in the CCSC cohort and have provided stored biospecimens. The collected samples and data provide important high-quality materials for research, discovery and evaluation related to CRC screening and carcinogenesis and is available for access by outside researchers. In addition to biological samples, the CCSC collects detailed patient information on their lifestyle, physical activity and dietary patterns through questionnaires at the time of their enrolment. Findings to date: The majority of participants (75%) are between 50 and 64 years of age. Women make up 46% (1055) of the cohort. Additional characteristics of the cohort included 44% reporting a body mass index of 25–30 kg/m 2 (overweight), 53% having never smoked tobacco and 13% having a family member with CRC. Future plans: The CCSC cohort plans to include the recruitment of high risk CRC cohorts. High-risk participants would comprise patients with a positive faecal immunochemical test and family history of CRC.